White blood cell global methylation and IL-6 promoter methylation in association with diet and lifestyle risk factors in a cancer-free population - Zhang, Fang Fang (Landes Bioscience, 2012)
Altered levels of global DNA methylation and gene silencing through methylation of promoter regions can impact cancer risk, but little is known about their environmental determinants. We examined the association between lifestyle factors and levels of global genomic methylation and IL-6 promoter methylation in white blood cell DNA of 165 cancer-free subjects, 18–78 years old, enrolled in the COMIR (Commuting Mode and Inflammatory Response) study, New York, 2009–2010. Besides self-administrated questionnaires on diet and physical activity, we measured weight and height, white blood cell (WBC) counts, plasma levels of high sensitivity C-reactive protein (hs-CRP), and genomic (LINE-1) and gene-specific methylation (IL-6) by pyrosequencing in peripheral blood WBC. Mean levels of LINE-1 and IL-6 promoter methylation were 78.2% and 57.1%, respectively. In multivariate linear regression models adjusting for age, gender, race/ethnicity, body mass index, diet, physical activity, WBC counts and CRP, only dietary folate intake from fortified foods was positively associated with LINE-1 methylation. Levels of IL-6 promoter methylation were not significantly correlated with age, gender, race/ethnicity, body mass index, physical activity or diet, including overall dietary patterns and individual food groups and nutrients. There were no apparent associations between levels of methylation and inflammation markers such as WBC counts and hs-CRP. Overall, among several lifestyle factors examined in association with DNA methylation, only dietary folate intake from fortification was associated with LINE-1 methylation. The long-term consequence of folate fortification on DNA methylation needs to be further evaluated in longitudinal settings.